2016
DOI: 10.1371/journal.pone.0149929
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Self-Prescribing Trends, Experiences and Attitudes in Upper Respiratory Tract Infection among Pharmacy and Non-Pharmacy Students: A Study from Lahore

Abstract: Pharmacists are the custodians of drugs; hence their education, training, behaviors and experiences would affect the future use of drugs at community and hospital pharmacies. Therefore, we aimed at evaluating the self-prescribing antibiotic trends, knowledge and attitudes among pharmacy and non-pharmacy students. We found that pharmacy students had higher risks of experiencing URIs related symptoms such as cough (RR; 1.7, p = 0.002), allergy (RR; 2.07, p = 0.03) and running nose (RR; 3.17, p<0.005), compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 24 publications
6
53
2
1
Order By: Relevance
“…Studies from different countries have been published showing a strong association between the consumption of and expenditure on antibiotics and the emergence of resistant microorganisms . Many WHO watch and reserve group antibiotics are consumed in developing countries like Pakistan for simple community‐acquired infections . The National Action Plan of Pakistan to fight against AMR was promulgated in May 2017.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from different countries have been published showing a strong association between the consumption of and expenditure on antibiotics and the emergence of resistant microorganisms . Many WHO watch and reserve group antibiotics are consumed in developing countries like Pakistan for simple community‐acquired infections . The National Action Plan of Pakistan to fight against AMR was promulgated in May 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In most developing countries, antibiotics are dispensed without prescription by physicians . Patients can easily access antibiotics that are life saving, because they are available over the counter (OTC) without prescription and their affordability is no longer an issue . Increased antibiotic self‐medication may be associated with the underutilisation of healthcare facilities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, incluso en estos profesionales, la prescripción puede ser inapropiada, por la formulación de antibióticos en infecciones que no la requieren o inadecuada en las que sí la requieren [4]. También, en farmacéu-ticos estudiantes [5] y profesionales, la autoprescripción de antibióticos es una práctica común asociada a aspectos como la educación y la experiencia [6].…”
Section: Introductionunclassified
“…Other factors include polypharmacy, co-morbidities, and age-related physiological changes that hamper patients' understanding of the use of the drug [7]. Among other major determinants of irrational drug use, self-prescribing of the prescription drugs such as antibiotics cannot be neglected and should be discouraged, to reduce the health and cost burden on the patient, and optimize the drug use in the community [8]. A study from Oman showed that 43 % of the population practiced selfmedication while 70 % stopped using medicine after the disappearance of symptoms [9].…”
Section: Introductionmentioning
confidence: 99%